Performance improvement of microbial fuel cells through assembling anodes modified with nanoscale materials. (2nd October 2022) - Liang, Huanhuan; Han, Jiali; Yang, Xingai; Qiao, Zhixing; Yin, Tao
In microbial fuel cell (MFC), the anode is the carrier of microbial attachment and growth, and its material and surface structure play a vital role in MFC electricity generation. Therefore, anode surface optimization is an effective way to improve MFC performance. Although the power generation of bacteria has been confirmed and studied as early as the beginning of the 20th century, up to now, MFC still has the extremely challenging problem of low current and low power output in practical application. To improve the performance of MFC, several strategies have been applied to enhance the bacterial extracellular electron transfer. One promising technology is the genetic engineering approach, and some outstanding research results have been obtained. Another effective strategy is to design and fabricate a high-performance electrode because anode material is the essential factor affecting MFC performance, which provides surface active sites for microbial adhesion, reproduction and interfacial electron transfer. At present, the MFC anodes mainly include carbon-based electrodes and a variety of metal electrodes, but untreated anodes have always been unable to overcome the obstacle of low power output. Anode modification, a common and effective method, is employed for improving the power output of MFC. For this reason, this review is primarily focused on the applications of various anode materials and its nanoscale modification in the field of MFC, including the influence of different anode materials on the power output of MFC, and analyzes the reasons why anode modification enhances output performance. Furthermore, the influence of anode research on the practical application of MFC in the future is prospected.